CLASSIFICATION OF ZOONYMIC PHRASEOLOGICAL UNITS BASED ON STRUCTURE AND MORPHOLOGY (International journal of artificial intelligence, 2026)
In this article, phraseological units with a zoonymic component are classified into groups according to their structural formation and the number of constituent components. Additionally, the morphological characteristics of the components within zoophrasemes are analyzed.